(untitled) (Journal of Universal Science Research, 2026)
Foreign investments represent an essential component of global economic development, contributing to capital formation, technological advancement, and international economic integration. In an increasingly interconnected world economy, improving mechanisms for attracting foreign investments has become a strategic priority for countries seeking sustainable growth and competitiveness. This article explores the conceptual foundations of foreign investment, examines key factors influencing investment flows, and analyzes institutional, economic, and policy-based mechanisms . The study identifies strategic directions for improving foreign investment mechanisms in alignment with digital economic development. Used to enhance investment attractiveness moreover, identifing effective approaches for improving foreign investment mechanisms within the broader context of global economic development.